Lifestyle Acquired Immunity, Decentralized Intelligent Infrastructures, and Revised Healthcare Expenditures May Limit Pandemic Catastrophe: A Lesson From COVID-19 - Ahmed, Asif; Haque, Tasnima; Rahman, Mohammad Mahmudur (Frontiers in Public Health, 2020)
Human race has often faced pandemic with substantial number of fatalities. As COVID-19 pandemic reached and endured in every corner on earth, even countries with moderate to strong healthcare support and expenditure seemed to struggle in containing disease transmission and casualties. COVID-19 affected countries have variability in demographic, socioeconomic and life style health indicators. At this context it is important to find out at what extent these parametric variations are actually modulating disease outcomes. To answer this, we have selected demographic, socioeconomic and health indicators e.g. population density, percentage of urban population, median age, health expenditure per capita, obesity, diabetes prevalence, alcohol intake, tobacco use, case fatality of non communicable diseases (NCDs) as independent variables. Countries were grouped according to these variables and influence on dependent variables e.g. COVID-19 test positive, case fatality and case recovery rates were statistically analyzed. The results suggested that countries with variable median age had significantly different outcome on test positive rate (P<0.01). Both median age (P=0.0397) and health expenditure per capita (P=0.0041) showed positive relation with case recovery. Increasing number of test per 100K population showed positive and negative relation with number of positives per 100K population (P=0.0001) and percentage of test positives (P<0.0001) respectively. Alcohol intake per capita in liter (P=0.0046), diabetes prevalence (P=0.0389) and NCDs mortalities (P=0.0477) also showed statistical relation with case fatality rate. Further analysis revealed that countries with high healthcare expenditure along with high median age and increased urban population showed more case fatality but also had better recovery rate. Investment in health sector alone is insufficient in controlling pandemic severity. Intelligent and sustainable healthcare both in urban and rural settings and healthy lifestyle acquired immunity may reduce disease transmission and comorbidity induced fatalities respectively.